The Solid-Liquid Mass Transfer Analysis for Delignification Process of Coffee Husk in Stirred Reactor - A Nandini; L Edahwati; S D Nurherdiana (Biomedical and Mechanical Engineering Journal (BIOMEJ), 2021)
The delignification process using the organosolv method is a process of removing lignin content by using organic solvents (such as ethanol). In this study, mass transfer analysis was used to determine the mass transfer coefficient of the delignification process of coffee husk. The first process was incubation process by using white rot fungi (Phanerochaete chrysosporium )in the coffee husk biomass, then followed by hydrolyzed process by using citric acid as a organosolv solvent. The delignification process were carried out under a conditions of temperature 50°C, solvent or etanol concentration 25%, speed range (500-700 rpm) and stirring time (1-4 hours with the gradient of 0,5 hours). The mass transfer effect was determined for different speed range and stirring time. From this research, the result of the mass transfer coefficient has range of 0.064/s – 0.46/s. The increasing of stirring time will affect to the mass transfer coefficient, which is also increasingly depend on the stirring time.